Pengaruh Kualitas Audit terhadap Keandalan Laporan Keuangan KSU Kencana Makmur Cabang Laren di Kabupaten Lamongan - Khusnul Khamidiyah (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2025)
This study aims to analyze the effect of audit quality on the reliability of financial statements at KSU Kencana Makmur, Laren Branch, Lamongan Regency. Audit quality is considered an important factor in enhancing users’ trust in financial statements by ensuring reliable, relevant, and fairly presented financial information. This research employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to management and employees involved in financial management. Data analysis was conducted using simple linear regression to determine the effect of audit quality on the reliability of financial statements. The results of this study are expected to provide practical implications for cooperatives in improving audit quality in order to produce more reliable and accountable financial statements. Keywords: audit quality, financial statement reliability, cooperative, audit